2021
DOI: 10.35741/issn.0258-2724.56.3.29
|View full text |Cite
|
Sign up to set email alerts
|

Disharmonization of Logistic Management and Regulation of Natural Disaster in Indonesia: A Collaborative Governance Perspective

Abstract: This research is at the ontological level of implementing logistic disaster management that is very significant in reducing the risk of natural disaster in Indonesia. The problem is very interesting to examine by conducting descriptive qualitative research. Sharpening the research was using the theory of public policy, collaborative governance, and supply chain management for logistics improvement. Data were collected using in-depth interviews with several key informants, direct observation, and related docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Likewise, Rustian et al (2021) indicated that supply management in public entities, here it is stated that it is the annual contracting plan that the government entity possesses having to comply with all the principles that govern all the contracting that is needed in the institution or is simply necessary to achieve the common welfare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Rustian et al (2021) indicated that supply management in public entities, here it is stated that it is the annual contracting plan that the government entity possesses having to comply with all the principles that govern all the contracting that is needed in the institution or is simply necessary to achieve the common welfare.…”
Section: Resultsmentioning
confidence: 99%
“…it as the attention with the right quantities, in the right conditions, delivered in the right place and at the right time, having to evaluate the costs of the goods in a correct and transparent way.Purchasing is immersed in logistics management as conceptualized byFerrara et al (2021), while for the dimension of supply management in public entities, the contribution ofRustian et al (2021) was used, and for the dimensions of storage and distribution, the knowledge ofFerrara et al (2021) was considered.…”
mentioning
confidence: 99%